Airborne Bacterial Community Composition According to Their Origin in Tenerife, Canary Islands - González-Martín, Cristina; Pérez-González, Carlos J.; González-Toril, Elena; Expósito, Francisco J.; Aguilera, Ángeles; Díaz, Juan P. (Frontiers in Microbiology, 2021)
Microorganisms are ubiquitous in the environment, and the atmosphere is no exception. However, airborne bacterial communities are some of the least studied. Increasing our knowledge about these communities and how environmental factors shape them is key to understanding disease outbreaks and transmission routes. We describe airborne bacterial communities at two different sites in Tenerife: La Laguna (urban, 600 m.a.s.l.) and Izaña (high mountain, 2,400 m.a.s.l.), and how they change throughout the year. Illumina MiSeq sequencing was used to target 16S rRNA genes in 293 samples. Results indicated a predominance of Proteobacteria at both sites (>65%), followed by Bacteroidetes, Actinobacteria and Firmicutes. Gammaproteobacteria were the most frequent within the Proteobacteria phylum during spring and winter, while Alphaproteobacteria dominated in the fall and summer. Within the 519 genera identified, Cellvibrio was the most frequent during spring (35.75%) and winter (30.73%); Limnobacter (24.49%) and Blastomonas (19.88%) dominated in the summer and Sediminibacterium represented 10.26% and 12.41% of fall and winter samples, respectively. Sphingomonas was also identified in 17.15% of the fall samples. These five genera were more abundant at the high mountain site, while other common airborne bacteria were more frequent at the urban site (Kocuria, Delftia, Mesorhizobium, Methylobacterium). Diversity values showed different patterns for both sites, with higher values during the cooler seasons in Izaña, whereas the opposite was observed in La Laguna. Regarding wind back trajectories, Tropical air masses were significantly different from African ones at both sites, showing the highest diversity and characterized by genera regularly associated with humans (Pseudomonas, Sphingomonas, Cloacibacterium), as well as others related to extreme conditions (Alicyclobacillus) or typically associated with animals (Lachnospiraceae). Marine and African air masses were consistent and very similar in their microbial composition. By contrast, European trajectories were dominated by Cellvibrio, Pseudomonas, Pseudoxanthomonas and Sediminibacterium. These data contribute to our current state of knowledge in the field of atmospheric microbiology. However, future studies are needed to increase our understanding of the influence of different environmental factors on atmospheric microbial dispersion and the potential impact of airborne microorganisms on ecosystems and public health.